Pronunciation Preferences Among Junior High School Students: A Comparative Study of American and British English Accents In SMP Students In Pematangsiantar - Gultom, Feronika; Simanjuntak, Iren Jelita; Sitorus, Cresia Seventri; Simbolon, Raldo Efraison Triven (CV Putra Publisher, 2025)
This research aims to identify students' tendencies in using American or British English accents when pronouncing English vocabulary. The subjects were eighth-grade students from a junior high school in Pematangsiantar. Data were collected through pronunciation tests and analyzed using phonetic transcription (IPA) to determine the type of accent used. Results showed that 73% of the tested words were pronounced with American English patterns, while 27% followed British English characteristics. Factors such as media exposure, teacher influence, and students’ perception of accents contributed to this trend. The study suggests the importance of teaching approaches that explicitly introduce accent variations in English language learning